Решить: 1. (3а-2b)·(9a²+6ab+4b²) 2. (3a+2b)·(9a²-6ab+4b²)

chamich chamich    2   18.06.2019 11:40    2

Ответы
Mocket Mocket  15.07.2020 06:53
1. Формула разности кубов: a^{3} - b^{3} = (a-b)( a^{2} +ab+ b^{2} )
В конкретном примере :(3a-2b)(9 a^{2} +6ab+4 b^{2} ) = (3a)^{3} - (2b)^{3} = 27 a^{3} - 8 b^{3} .

2. Аналогично, формула суммы кубов: a^{3} + b^{3} = (a+b)( a^{2} -ab+ b^{2} )
В конкретном примере :(3a+2b)(9 a^{2} -6ab+4 b^{2} ) = (3a)^{3} + (2b)^{3} = 27 a^{3} + 8 b^{3} .
ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Алгебра